Relasi Agama dan Masyarakat dalam Perspektif John Hick dan Gus Dur: Pluralisme Agama - Nanda Khairiyah (Sekolah Tinggi Agama Islam AL Aqidah Al Hasyimiyyah Jakarta, 2022)
Discussions related to the views of religious pluralism often attract many parties, ranging from academics, officials as well as religious figures. This discussion often has biases in society which can often trigger social conflicts. This paper in the frame of academics tries to provide its treasures related to the views of 2 Pluralistic Religious figures with different religious backgrounds. Gus Dur or Abdurrahman Wahid is the 4th (four) President of Indonesia is not only a political figure but also a religious figure who often shares his scientific views regarding Pluralism. Gus Dur is a Muslim-Traditionalist representative who carries the idea of Pluralism in the midst of a heterogeneous Indonesian society. Likewise, John Hick was born into a Christian environment who at the beginning of his spiritual journey recognized religious exclusivity. John Hick had a profound spiritual experience while studying other religions including Islam, Buddhism and others. This paper hopefully can provide enlightenment regarding how people are able to understand the concept of Religious Pluralism through these 2 religious figures.